Three-Dimensional Visualization Algorithm Simulation of Construction Management Based on GIS and VR Technology. (2nd February 2021) - Xu, Shuhong
Abstract : With the development and application of information technology, the digitization of information management and the virtualization of physical models have become very important technical application fields in the world. The establishment of the 3D landscape model and the realization of the 3D geographic information system (GIS) are based on this, and there is not only a wide range of development prospects in many aspects such as urban planning and management, planning and design, local government construction, housing industry development, land monitoring and management, and environmental monitoring and evaluation. There are not only research studies and formulations but also a practical significance in other analysis, evaluation, decision making, and other departments. In recent years, the research of 3D city modeling has been developed rapidly, and most of the existing 2D-GIS can be transformed into 3D visual landscape. Based on the three-dimensional geographic information system and desktop drawing software AutoCAD, this paper takes the two-dimensional line drawing (DLG) of a residential district as the base map, expounds the design process of the three-dimensional simulation model of the urban community from the aspects of map preprocessing, building simulation model construction, texture mapping, and virtual visualization, and discusses the problems encountered in it. The main contributions of this paper are that this technology puts forward a new solution for the integrated corridor operation and maintenance management, greatly improves the intelligent management level of the integrated corridor operation and maintenance work, and simplifies the complex integrated corridor operation and maintenance management. It is helpful to improve the work efficiency of operation and maintenance, reduce the dependence of personnel, and respond to the long-term construction needs of the smart city at the same time.